Mapping Safety, Security and Walkability of Historical Public Open Spaces in Post-Conflict Libya: Tripoli as North African Case Study - Abdulla, Khairi; Abdelmonem, Mohamed Gamal (Alanya Üniversitesi, 2023)
North African cities have been undergoing major transformation over the past two decades following protracted instability, civic uprising, and conflicts, changing their perception from havens to territories of displacements with social, psychological, and physical problems. Historic public spaces in those cities, in particular, form a critical part of urban environments as they have the identity, livelihoods and cross-community engagement in a healthy and fulfilling urban fabric and culture. Whilst there have been several studies on the characteristics of open spaces in urban environments, there is very limited work on the changing perceptions, use and engagement of public spaces in historic cities especially in the post-Arab Spring and its relative instability. This study aims to deploy investigative and creative methods to map, analyse and navigate through the transformation in the perceptions of historic public spaces in Post-Conflict Libya and its divided cities. It will study the users' (locals and visitors) attitudes, movements, and reflections on how those spaces have changed over time. visitors' behaviour in open historical public spaces in Tripoli, Libya. The study explores the relationships between the characteristics of historical public spaces, physical activity, and psychological behaviour. The paper argues that safety and security in public spaces are critical and inherent qualities that inform much of the users’ attitudes in historic cities, which has continued to be the case in post-conflict Tripoli.